The Globalization of Strangeness - Rumford, C (Palgrave Macmillan, 2020)
The figure of the stranger is in serious need of revision, as is our understanding of the society against which the stranger is projected. Under conditions of globalization, inside/outside markers have been eroded and conventional indicators of 'we-ness' are no longer reliable. We now live in a generalized state of strangeness, one consequence of globalization: we no longer know where our community ends and another one begins. In such circumstances it is often the case that neighbours are the nearest strangers. Strangeness occurs when global consciousness outstrips global connectivity and this means that we need to rethink some core elements of globalization theory. Under conditions of strangeness the stranger is a 'here today, gone tomorrow' figure. This book identifies the cosmopolitan stranger as the most significant contemporary figure of the stranger, one adept at negotiating the 'confined spaces' of globalization in order to promote new forms of social solidarity and connect with distant others.